Method for improving corrosion resistance of chemical silver coating on surface of aramid fiber

Through swelling-embedded nano-silver modification pretreatment and electric field-assisted composite electroless plating technology, the corrosion problem of aramid fiber silver plating is solved, forming a silver-graphene composite plating with good conductivity, improving corrosion resistance and conductivity. It meets the requirements of flame retardant and conductive properties, and realizes low-cost, green and environmentally friendly electromagnetic shielding materials.

CN119194847APending Publication Date: 2024-12-27SHAOXING RES INST OF SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302553.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The aramid fiber silver coating is susceptible to corrosive media such as sulfides and cyanides in the atmosphere and ultraviolet radiation, which affects the conductivity. The existing protection methods include poor conductivity of organic protective agents, high protection costs of precious metals, and non-conductive inorganic protective films. Poor flexibility makes it difficult to meet the requirements of flame retardant and conductive properties.

Method used

The swell-embedded nanosilver modification pretreatment was used to construct a silver conductive layer, and the silver-graphene composite coating was coated on the surface of the aramid fiber through electric field-assisted composite electroless plating to form a protective film with good conductivity.

Benefits of technology

The corrosion resistance of the electroless silver-plating layer on the surface of aramid fiber is improved, the mechanical properties of the fiber are maintained, the use of precious metals is avoided, and the low-cost, green and environmentally friendly improvement of conductivity and flame retardancy is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194847A_ABST
    Figure CN119194847A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the corrosion resistance of a chemical silver-plated layer on the surface of an aramid fiber, and aims to coat the surface of the silver-plated aramid fiber with graphene to block a corrosive medium and keep the conductivity, the corrosion resistance, the antibacterial property and other properties of the silver-plated fiber not attenuated. The preparation method comprises the following steps: performing'swelling-embedding 'nano-silver modification pretreatment, then constructing a silver conductive layer on the surface of the aramid fiber through a chemical pre-plating silver layer, and finally coating the surface with a silver-graphene composite plating layer through electric field assisted composite chemical plating. The durable anti-corrosion method which can protect the chemical silver plating layer and does not affect the flame retardance and the conductivity of the fabric is simple in process and low in cost, and is the key to the application of the conductive aramid fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the corrosion resistance of a chemical silver-plated layer on the surface of aramid fiber. Background Art

[0002] With the rapid development of electronic and information technology, the electromagnetic interference problem caused by electromagnetic waves is becoming increasingly serious. Electromagnetic radiation not only interferes with the normal operation of electrical equipment, but also poses a serious threat to human health. Therefore, the development of reliable and high-performance electromagnetic shielding materials is of great significance for improving the safety and reliability of electronic products and equipment, ensuring the safety and smooth operation of information communication systems, network systems, transmission systems, weapon platforms, etc., and protecting human health and the surrounding environment.

[0003] Flexible electromagnetic shielding fabrics are key materials that need to be urgently addressed in personal protection and aerospace lightweighting. Aramid fiber has excellent properties such as high strength, light weight, high temperature resistance, acid and alkali resistance, etc. The conductive fiber prepared by selecting aramid as the matrix can be used in aerospace, submarines, cables, biomedicine and many other fields. The methods of fiber metallization include chemical vapor deposition, chemical plating, magnetron sputtering, electroplating, etc. The preparation of silver-plated aramid conductive fiber using chemical plating technology is not only low-cost, simple in process, and easy to industrialize, but also the prepared conductive fiber is light in weight and has excellent mechanical properties, heat resistance, corrosion resistance and conductivity. The silver coating is easily corroded by corrosive media such as sulfide and cyanide in the atmosphere and ultraviolet radiation, which seriously affects the conductive properties of the silver coating. Therefore, it is necessary to protect the silver coating of aramid fiber. The most widely used protection method is (1) coating an organic protective agent to form an organic complex passivation film to isolate the silver from the contact with the corrosive medium. However, the film layer formed by organic protective agents has poor thermal stability and poor bonding with the substrate, which has a certain impact on the flame retardancy, conductivity and durability of aramid fiber fabrics. (2) Metal protection: Deposit a layer of precious metals such as titanium, gold, platinum, palladium and other metals on the surface of silver. This method is generally deposited by magnetron sputtering, etc., with complex processes and low cost performance. (3) Inorganic protective films. This type of film has good corrosion resistance, but this method involves high-temperature treatment and is not suitable for aramid fiber protection. In addition, the protective film is not conductive and has poor flexibility.

[0004] As a nanomaterial, graphene has many excellent properties, such as high electrical conductivity, high thermal conductivity, high aspect ratio, large specific surface area, rich functional groups, ultra-light weight, and stable chemical properties. It has great application potential in electromagnetic shielding materials. At the same time, graphene can effectively block the passage of gas atoms such as water vapor and oxygen. Graphene itself also has good anti-corrosion properties and can block corrosive media. Graphene can passivate with the base metal to form a protective film layer to enhance the protection ability. Graphene sheets have strong electrical conductivity and can inhibit the anode reaction, thereby slowing down the corrosion of the metal. Therefore, coating the graphene coating on the surface of the chemical silver plating layer of aramid fiber has excellent physical barrier and barrier properties, which can play a good protective role on the metal matrix, and at the same time can enhance the flame retardancy, conductivity and durability of the aramid fiber.

[0005] The prior application documents are as follows:

[0006] (1) Chemical composite plating solution and preparation method thereof (CN 114855151B): The present invention mainly realizes chemical composite nickel plating, and the chemical composite plating solution includes the following components: nickel salt, reducing agent, complexing agent, stabilizer, surfactant, molybdate, cerium oxide powder and graphene oxide powder.

[0007] The invention has the following disadvantages: 1. Graphene only improves the coating performance but does not form an anti-corrosion coating; 2. Graphene is not deposited in a directional manner, the resulting graphene is randomly distributed, and the film coverage is not strong; 3. This method is a chemical Ni-P plating and does not involve chemical silver plating.

[0008] (2) A corrosion inhibitor for passivating the surface of silver-plated copper wire and a method of use (licensing announcement number CN114921787B): First, the surface of the silver-plated copper wire is preliminarily passivated, that is, the silver-plated copper wire is first passivated in a corrosion inhibitor of a mixture of trivalent chromium salt and trivalent cobalt salt, taken out, cleaned and dried, and then passivated in a corrosion inhibitor of a mixture of organic phosphoric acid and alkyl mercaptan, taken out, dried, and aged at room temperature for 24 hours.

[0009] The organic protective agent in the invention has the following disadvantages: 1. The organic protective agent has poor conductivity; 2. The organic protective agent is easy to age; 3. The flame retardant performance of the organic protective agent is poor. Therefore, it is not suitable for electromagnetic shielding conductive fibers that require both flame retardancy and conductivity.

[0010] (3) Silver-plated fiber with anti-tarnishing layer and its preparation method (CN 101725036 B): Silver is plated on the surface of the fiber by magnetron sputtering, and then in the same coating environment, metal elements such as titanium, gold, platinum, palladium or alloys that are chemically stable and not easily deteriorated in the air are formed into a thin film and attached to the surface of the silver-plated layer.

[0011] The invention has the following disadvantages: 1. The magnetron sputtering equipment is expensive and the coating process is complicated; 2. The coating cost of precious metals is relatively high; 3. Due to the skin effect of the conductor, the composite coating cannot fully exert the good conductivity of silver, thereby reducing the conductivity of the silver-plated fiber.

[0012] (4) An intermediate for preventing silver from discoloration, a composition, anti-discoloration silver and a preparation method (CN 109338340B): Boric acid and an organic solution of ethyl orthosilicate are mixed, and then mixed with bismuth nitrate to obtain an intermediate for preventing silver from discoloration; silver is soaked in the intermediate for preventing silver from discoloration and then taken out to form an intermediate layer on the surface of the silver; the intermediate layer is heat-treated by first heating and then cooling to obtain a silicon dioxide, boron trioxide and bismuth trioxide glass layer to prevent silver from corrosion.

[0013] The invention has the following disadvantages: 1. The method has a complicated process and involves high-temperature treatment, which exceeds the temperature resistance of aramid fiber; 2. Glass oxide is not conductive; 3. Glass oxide is very brittle, which affects the flexibility of silver-plated fiber. Summary of the invention

[0014] In order to solve the above problems existing in the prior art, the present invention proposes a method for improving the corrosion resistance of the chemical silver-plated layer on the surface of aramid fiber.

[0015] The present invention is specifically implemented through the following technical solutions:

[0016] A method for improving the corrosion resistance of a chemical silver-plated layer on the surface of an aramid fiber, comprising:

[0017] 1) Firstly, pre-treatment by “swelling-embedding” nanosilver modification;

[0018] 2) then constructing a silver conductive layer on the surface of the aramid fiber by chemically pre-plating a silver layer;

[0019] 3) Finally, a silver-graphene composite coating is coated on the surface by electric field assisted composite chemical plating.

[0020] Furthermore, the step 1) "swelling-embedding" nanosilver modification pretreatment includes:

[0021] 1) Degreasing: Use acetone or anhydrous ethanol to remove the residual grease or pollutants on the surface of the aramid fiber;

[0022] 2) Swelling embedding: preparing a silver salt solution containing silver nitrate, and the solvent is at least one of dimethyl sulfoxide and N-methylpyrrolidone, and injecting the silver ions of the catalyst into the epidermis of the fiber;

[0023] 3) Reduction: The aramid fiber with Ag ions implanted on the surface is immersed in an aqueous solution of sodium borohydride to reduce the AgNO3 on the fiber surface to metallic Ag particles, which will serve as a catalyst for the chemical plating reaction.

[0024] Furthermore, the degreasing step 1) is specifically to immerse the aramid fiber in acetone or anhydrous ethanol solution (pure solution 100%) for 0.5-2 hours, and then wash it repeatedly with deionized water and dry it at 40-60° C. for 3-10 hours.

[0025] Furthermore, in the step 2) swelling and embedding, the silver nitrate in the silver salt solution is 0.1-0.2 mol / L, the volume ratio of the solvent to water is 1:1, and the silver ions of the catalyst are injected into the epidermis of the fiber at a temperature of 90°C.

[0026] Furthermore, in the step 3), the aqueous solution of sodium borohydride in the reduction is 5-10 g / L, the reduction time is 15-30 min, and the temperature is room temperature.

[0027] Furthermore, the step 2) specifically comprises: firstly preparing a silver salt solution A and a reducing agent solution B respectively, then mixing the two to obtain a chemical plating solution C, and finally The fabric is placed in chemical plating solution C and plated at 25-30°C for 0.5-3h to obtain a silvery white Silver plated fabric.

[0028] Furthermore, the silver salt solution A comprises AgNO3, 25% ammonia water, ethylenediamine and KOH, with a specific ratio of 2-6:15-30:5-10:2-5 g / L.

[0029] Furthermore, the reducing agent solution B contains glucose, sodium tartrate, ethanol and polyethylene glycol, with a specific ratio of 2-5: 1-3: 15-25: 5-10 g / L.

[0030] Furthermore, the chemical plating in step 3) specifically includes:

[0031] 1) Silver-graphene composite chemical plating: 0.01-0.05 g / L of a surfactant is added to deionized water and stirred evenly, then 10-50 mg / L of graphene is added, and the mixture is mechanically stirred evenly under the action of ultrasound to form a solution D, and the solution D is slowly added to the solution C and mechanically stirred under ultrasonic vibration to obtain a composite chemical plating solution E;

[0032] 2) Electric field assisted composite chemical plating: Pour the composite chemical plating solution E into the aqueduct, The silver-plated fabric is wound on a polytetrafluoroethylene frame in a direction parallel to the electric field. The power is turned on to apply the electric field. The aqueduct is equipped with ultrasonic and mechanical stirring devices to keep the plating solution stable and uniform.

[0033] Furthermore, the surfactant is at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.

[0034] The present invention has the following beneficial effects:

[0035] 1. The "swelling and embedding" nano-silver modification method can implant nano-scale silver particles into the fiber surface. The particles are both a catalyst for the growth of the coating and an anchor for the coating. This method can solve the problem that aramid fibers are difficult to metallize. The coating is firm and the mechanical properties of the fiber are maintained to the maximum extent. At the same time, the use of metal palladium is avoided, which is green, environmentally friendly and low-cost.

[0036] 2. Using the silver-graphene composite chemical plating method, the graphene solution and the chemical plating solution are mixed to simultaneously deposit the silver-graphene composite coating;

[0037] 3. At the same time, adding an electric field during the mixed chemical plating can make the randomly suspended graphene sheets oriented in the solution, and form a flatly arranged graphene coating on the fiber surface during the chemical silver plating. This coating has good conductivity and can also better exert the barrier, antibacterial and corrosion resistance of graphene to protect the silver plating. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a flow chart of the present invention;

[0039] Figure 2 Schematic diagram of the electric field assisted composite chemical plating structure of the present invention; 1. Chemical plating tank; 2. Polytetrafluoroethylene fixing frame; 3. Pre-silvered aramid fiber; 4. DC power supply

[0040] Figure 3 This is a cross-sectional view of the silver-plated aramid fiber of the present invention. 1. Aramid fiber; 2. Pre-silver-plated layer; 3. Silver-graphene composite coating DETAILED DESCRIPTION

[0041] The following describes the implementation of the present invention through specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0042] like Figure 1As shown, the present invention firstly performs a pretreatment of nano silver modification by "swelling-embedding", then constructs a silver conductive layer on the surface of the aramid fiber by a chemical pre-plating silver layer, and finally coats the surface with a silver-graphene composite coating by composite chemical plating. In particular, in order to ensure that graphene can be laid flat on the coating surface, the directional arrangement of graphene nanosheets is achieved by utilizing the action of electric field force. The specific method is as follows: the silver-plated conductive aramid fiber is wound on a polytetrafluoroethylene frame according to a certain rule and placed in a chemical plating tank. The chemical tank has a direct current electric field, and the direction of the direct current electric field is parallel to the fiber direction, so that the randomly suspended graphene sheets can be oriented in the solution. While chemically plating silver, a flatly arranged graphene coating is formed on the fiber surface. The coating has good conductivity and can also better exert the barrier property and corrosion resistance of graphene to protect the silver coating.

[0043] 1. Aramid fiber pretreatment

[0044] (1) Degreasing: Use acetone or anhydrous ethanol to remove the residual grease or pollutants on the surface of the aramid fiber. Immerse the aramid fiber in acetone or anhydrous ethanol solution for 0.5-2 hours, then rinse it repeatedly with deionized water and dry it at 40-60℃ for 3-10 hours.

[0045] (2) Swelling embedding: Prepare a silver salt solution containing silver nitrate and a solvent of at least one of dimethyl sulfoxide and N-methylpyrrolidone (0.1-0.2 mol / L AgNO3, V H2O :V (DMSO、NMP) =1:1) for 3 hours at a temperature of 90°C in order to inject the catalyst Ag ions into the fiber epidermis.

[0046] (3) Reduction: The aramid fiber with AgNO3 implanted on the surface is immersed in an aqueous solution of sodium borohydride (5-10 g / L NaBH4) for 15-30 min at room temperature to reduce the AgNO3 on the fiber surface to metallic Ag particles, which will serve as a catalyst for the chemical plating reaction.

[0047] 2. Chemical plating

[0048] The specific experimental operation process is as follows:

[0049] (1) Chemical silver plating:

[0050] In order to ensure the stability of the plating solution, silver salt solution A (AgNO3, 25% ammonia water, ethylenediamine and KOH) and reducing agent solution B (glucose, sodium tartrate, ethanol and polyethylene glycol) were prepared separately, and then the two were mixed to obtain chemical plating solution C. Finally, the pretreated The fabric is placed in chemical plating solution C and plated at 25-30°C for 0.5-3h to obtain a silvery white Silver plated fabric.

[0051] Table 3-1 Chemical compositions and process conditions

[0052]

[0053] (2) Silver-graphene composite chemical plating: 0.01-0.05 g / L of a surfactant (at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate) is added to deionized water and stirred evenly, and then 10-50 mg / L of graphene is added and mechanically stirred evenly under the action of ultrasonic waves to form a solution D. Solution D is slowly added to solution C and mechanically stirred under ultrasonic vibration to obtain a composite chemical plating solution E.

[0054] (3) Electric field assisted composite chemical plating: Pour the composite chemical plating solution E into the aqueduct, wind the aramid fiber 3 on the polytetrafluoroethylene frame 2 in the direction parallel to the electric field, turn on the power supply 4 to apply the electric field, and equip the aqueduct 1 with ultrasonic and mechanical stirring devices to keep the plating solution stable and uniform. Figure 2 shown.

[0055] The final silver-coated aramid fiber is Figure 3 As shown, the surface of the aramid fiber 1 includes two coating layers, namely a pre-silver coating layer 2 and a silver-graphene composite coating layer 3. The coating has good bonding strength with the fiber, is uniform, and has good corrosion resistance.

[0056] Case 1

[0057] 1. Aramid fiber pretreatment

[0058] (1) Degreasing: Use acetone or anhydrous ethanol to remove the residual grease or contaminants on the surface of the aramid fiber. After immersing the aramid fiber in an acetone solution for 0.5 h, wash it repeatedly with deionized water and dry it at 40 °C for 10 h.

[0059] (2) Swelling embedding: Prepare a silver salt solution containing silver nitrate and dimethyl sulfoxide (0.1 mol / L AgNO3, V H2O :V (DMSO) =1:1) for 3 hours at a temperature of 90°C in order to inject the catalyst Ag ions into the fiber epidermis.

[0060] (3) Reduction: The aramid fiber with AgNO3 implanted on the surface is immersed in an aqueous solution of sodium borohydride (8 g / L NaBH4) for 30 min at room temperature to reduce the AgNO3 on the fiber surface to metallic Ag particles, which will serve as a catalyst for the chemical plating reaction.

[0061] 2. Chemical plating

[0062] The specific experimental operation process is as follows:

[0063] (2) Chemical silver plating:

[0064] In order to ensure the stability of the plating solution, silver salt solution A (AgNO3, 25% ammonia water, ethylenediamine and KOH, the ratio is 2:15:5:2g / L) and reducing agent solution B (glucose, sodium tartrate, ethanol and polyethylene glycol, the ratio is 2:1:15:5g / L) are prepared respectively, and then the two are mixed to obtain chemical plating solution C. Finally, the pretreated The fabric was placed in chemical plating solution C and plated at 25°C for 0.5 h to obtain a silvery white Silver plated fabric.

[0065] (2) Silver-graphene composite chemical plating: 0.01 g / L of surfactant (sodium dodecylbenzene sulfonate) was added to deionized water and stirred evenly. Then 10 mg / L of graphene was added and mechanically stirred evenly under the action of ultrasonic wave to form solution D. Solution D was slowly added to solution C and mechanically stirred under ultrasonic vibration to obtain composite chemical plating solution E.

[0066] (3) Electric field assisted composite chemical plating: The composite chemical plating solution E is poured into the aqueduct, and the aramid fiber is wound on the polytetrafluoroethylene frame in the direction parallel to the electric field. The power is turned on to apply the electric field. The aqueduct is equipped with ultrasonic and mechanical stirring devices to keep the plating solution stable and uniform.

[0067] Case 2

[0068] 1. Aramid fiber pretreatment

[0069] (1) Degreasing: Use acetone or anhydrous ethanol to remove the residual grease or contaminants on the surface of the aramid fiber. After immersing the aramid fiber in anhydrous ethanol solution for 1 hour, it is repeatedly washed with deionized water and dried at 50°C for 6 hours.

[0070] (2) Swelling embedding: Prepare a silver salt solution containing silver nitrate and a solvent of N-methylpyrrolidone solution (0.2 mol / L AgNO3, V H2O :V (NMP) =1:1) for 3 hours at a temperature of 90°C in order to inject the catalyst Ag ions into the fiber epidermis.

[0071] (3) Reduction: The aramid fiber with AgNO3 implanted on the surface is immersed in an aqueous solution of sodium borohydride (8 g / L NaBH4) for 20 min at room temperature to reduce the AgNO3 on the fiber surface to metallic Ag particles, which will serve as a catalyst for the chemical plating reaction.

[0072] 2. Chemical plating

[0073] The specific experimental operation process is as follows:

[0074] (3) Chemical silver plating:

[0075] In order to ensure the stability of the plating solution, silver salt solution A (AgNO3, 25% ammonia water, ethylenediamine and KOH, the ratio is 5:20:8:3g / L) and reducing agent solution B (glucose, sodium tartrate, ethanol and polyethylene glycol, the ratio is 3:2:20:8g / L) are prepared respectively, and then the two are mixed to obtain chemical plating solution C. Finally, the pretreated The fabric was placed in chemical plating solution C and plated at 30°C for 2 h to obtain a silvery white Silver plated fabric.

[0076] (2) Silver-graphene composite chemical plating: 0.02 g / L of surfactant (sodium dodecyl sulfate) was added to deionized water and stirred evenly, and then 20 mg / L of graphene was added and mechanically stirred evenly under the action of ultrasound to form a solution D. Solution D was slowly added to solution C and mechanically stirred under ultrasonic vibration to obtain a composite chemical plating solution E.

[0077] (3) Electric field assisted composite chemical plating: The composite chemical plating solution E is poured into the aqueduct, and the aramid fiber is wound on the polytetrafluoroethylene frame in the direction parallel to the electric field. The power is turned on to apply the electric field. The aqueduct is equipped with ultrasonic and mechanical stirring devices to keep the plating solution stable and uniform.

[0078] Case 3:

[0079] 1. Aramid fiber pretreatment

[0080] (1) Degreasing: Use acetone or anhydrous ethanol to remove the residual grease or contaminants on the surface of the aramid fiber. After immersing the aramid fiber in an acetone solution for 2 hours, it is repeatedly washed with deionized water and dried at 60°C for 3 hours.

[0081] (2) Swelling embedding: Prepare a silver salt solution containing silver nitrate, a solvent of dimethyl sulfoxide and N-methylpyrrolidone mixed solution (ratio 1:1), (0.2 mol / L AgNO3, V H2O :V (DMSO、NMP) =1:1) for 3 hours at a temperature of 90°C in order to inject the catalyst Ag ions into the fiber epidermis.

[0082] (3) Reduction: The aramid fiber with AgNO3 implanted on the surface is immersed in an aqueous solution of sodium borohydride (10 g / L NaBH4) for 15 min at room temperature to reduce the AgNO3 on the fiber surface to metallic Ag particles, which will serve as a catalyst for the chemical plating reaction.

[0083] 2. Chemical plating

[0084] The specific experimental operation process is as follows:

[0085] (1) Chemical silver plating:

[0086] In order to ensure the stability of the plating solution, silver salt solution A (AgNO3, 25% ammonia water, ethylenediamine and KOH, the ratio is 6:30:10:5g / L) and reducing agent solution B (glucose, sodium tartrate, ethanol and polyethylene glycol, the ratio is 5:3:25:10g / L) are prepared respectively, and then the two are mixed to obtain chemical plating solution C. Finally, the pretreated The fabric was placed in chemical plating solution C and plated at 30°C for 3 h to obtain a silvery white Silver plated fabric.

[0087] (2) Silver-graphene composite chemical plating: 0.05 g / L of surfactant (sodium dodecyl sulfate) was added to deionized water and stirred evenly, and then 50 mg / L of graphene was added and mechanically stirred evenly under the action of ultrasound to form a solution D. Solution D was slowly added to solution C and mechanically stirred under ultrasonic vibration to obtain a composite chemical plating solution E.

[0088] (3) Electric field assisted composite chemical plating: The composite chemical plating solution E is poured into the aqueduct, and the aramid fiber is wound on the polytetrafluoroethylene frame in the direction parallel to the electric field. The power is turned on to apply the electric field. The aqueduct is equipped with ultrasonic and mechanical stirring devices to keep the plating solution stable and uniform.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber, characterized in that: include: 1) Firstly, pre-treatment with nanosilver modification by "swelling-embedding"; 2) then constructing a silver conductive layer on the surface of the aramid fiber by chemically pre-plating a silver layer; 3) Finally, a silver-graphene composite coating is coated on the surface by electric field assisted composite chemical plating.

2. A method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 1, characterized in that: The step 1) "swelling-embedding" nanosilver modification pretreatment comprises: 1) Degreasing: Use acetone or anhydrous ethanol to remove the residual grease or pollutants on the surface of the aramid fiber; 2) Swelling embedding: preparing a silver salt solution containing silver nitrate, and the solvent is at least one of dimethyl sulfoxide and N-methylpyrrolidone, and injecting the silver ions of the catalyst into the epidermis of the fiber; 3) Reduction: The aramid fiber with Ag ions implanted on the surface is immersed in an aqueous solution of sodium borohydride to reduce the AgNO3 on the fiber surface to metallic Ag particles, which will serve as a catalyst for the chemical plating reaction.

3. A method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 2, characterized in that: The degreasing step 1) specifically comprises immersing the aramid fiber in an acetone or anhydrous ethanol solution for ultrasonic treatment for 0.5-2 hours, repeatedly washing with deionized water, and drying at 40-60° C. for 3-10 hours.

4. The method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 2, characterized in that: In the step 2) swelling and embedding, the silver nitrate in the silver salt solution is 0.1-0.2 mol / L, the volume ratio of the solvent to water is 1:1, and the silver ions of the catalyst are injected into the epidermis of the fiber at a temperature of 90°C.

5. The method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 2, characterized in that: In the step 3), the aqueous solution of sodium borohydride is 5-10 g / L, the reduction time is 15-30 min, and the temperature is room temperature.

6. The method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 1, characterized in that: The step 2) specifically comprises: firstly preparing silver salt solution A and reducing agent solution B respectively, then mixing the two to obtain chemical plating solution C, and finally mixing the pre-treated solution in step 1) The fabric is placed in chemical plating solution C and plated at 25-30°C for 0.5-3h to obtain a silvery white Silver plated fabric.

7. A method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 6, characterized in that: The silver salt solution A comprises AgNO3, 25% ammonia water, ethylenediamine and KOH, with a specific ratio of 2-6:15-30:5-10:2-5 g / L.

8. The method for improving the corrosion resistance of the chemical silver-plated layer on the surface of aramid fiber according to claim 7, characterized in that: The reducing agent solution B contains glucose, sodium tartrate, ethanol and polyethylene glycol, with a specific ratio of 2-5: 1-3: 15-25: 5-10 g / L.

9. A method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 8, characterized in that: The step 3) in which chemical plating is performed specifically includes: 1) Silver-graphene composite chemical plating: 0.01-0.05 g / L of a surfactant is added to deionized water and stirred evenly, then 10-50 mg / L of graphene is added, and the mixture is mechanically stirred evenly under the action of ultrasound to form a solution D, and the solution D is slowly added to the solution C and mechanically stirred under ultrasonic vibration to obtain a composite chemical plating solution E; 2) Electric field assisted composite chemical plating: Pour the composite chemical plating solution E into the aqueduct, The silver-plated fabric is wound on a polytetrafluoroethylene frame in a direction parallel to the electric field. The power is turned on to apply the electric field. The aqueduct is equipped with ultrasonic and mechanical stirring devices to keep the plating solution stable and uniform.

10. A method for improving the corrosion resistance of the chemical silver plating layer on the surface of aramid fiber according to claim 9, characterized in that: The surfactant is at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.